2021
DOI: 10.1007/s00417-021-05436-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a combination of augmented MicroPulse and limited Continuous Wave Cyclophotocoagulation in patients with refractory glaucoma

Abstract: Purpose To assess the safety and effectiveness of augmented MicroPulse (MP-TSCPC) with limited Continuous Wave Transscleral Cyclophotocoagulation (CW-TSCPC) in patients with refractory glaucoma. Methods Thirty-eight eyes of 38 patients underwent combined MP-TSCPC and CW-TSCPC at Massachusetts Eye and Ear. Kaplan–Meier survival curves and Wilcoxon paired sign rank tests were performed to evaluate intraocular pressure (IOP), glaucoma medication burden, best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Destructive laser energy is delivered continuously to the ciliary body to reduce aqueous humor production in CW-TSCPC. MP-TSCPC utilizes repetitive pulses of energy separated by periods of rest to achieve more targeted treatment of pigmented tissue in the ciliary processes and minimize collateral damage to neighboring tissues [ 10 ]. CW-TSCPC is effective in reducing IOP and medication burden in refractory glaucoma cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Destructive laser energy is delivered continuously to the ciliary body to reduce aqueous humor production in CW-TSCPC. MP-TSCPC utilizes repetitive pulses of energy separated by periods of rest to achieve more targeted treatment of pigmented tissue in the ciliary processes and minimize collateral damage to neighboring tissues [ 10 ]. CW-TSCPC is effective in reducing IOP and medication burden in refractory glaucoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gupta et al describing the outcomes of this combination technique found a 16.5 mmHg and 17.9 mmHg mean drop in IOP at 12 and 18 months, respectively. The average medication burden decreased from 3.8 to 1.7 at 18 months, and no long-term sight-threatening complications were observed [ 10 ]. This technique thus limits the side effects related to CW-TSCPC while maintaining a satisfactory efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the power used ranged from 1750-2000mW in various studies [14][15][16]. As this study incorporated two different institutions and multiple attending surgeons before the publication of augmented setting for MPCPC [17,18], there were significant variations in power and duration chosen, which are lower than the recently published guidelines. There was a trend towards higher power and the duration on the MPCPC being associated with greater success, but this was not statistically significant (Fig 2).…”
Section: Plos Onementioning
confidence: 99%
“…W e report the case of severe mixed-mechanism glaucoma observed in a monocular Axenfeld-Rieger syndrome (ARS) patient who was successfully managed with an ahmed glaucoma implant (AGI) followed by a novel technique described as augmented MicroPulse transscleral cyclophotocoagulation (MP-TSCPC) [1] . ARS encompasses a heterogeneous spectrum of diseases involving anterior segment dysgenesis and systemic developmental anomalies [2] .…”
Section: Dear Editormentioning
confidence: 99%